(untitled) (Journal of the College of Basic Education, 2022)
SCAMPER strategy involves seven basic skills, namely: (Substitute, Combine, Adapt, Modify, Magnify, Minify, put to other uses, Eliminate, Reveres, Rearrange). The researcher aims at identify "The Effect of Using SCAMPER Strategy in the Achievement Mathematics for fifth _ primary school students." The following zero hypotheses were formulated to achieve the objective: _there is no statistically significant differences at the level of sign if icon (0.05) between the mean scores of experimental group who were taught in the (SCAMPER) Strategy and the mean scores of the control group taught according to the normal method in the achievement test of mathematics. The research is limited to fifth primary pupils at the primary schools / directorate general of Education / 1st. Al – karkh for academic year (2013 – 2014) . It is also limited to the sections that deal with (Fractions, operations on fractions, decimals) of their prescribed textbook . The researcher has selected the experimental design of partial control for two groups – one experimental and one control with a post – test - . Dar – Al – Manual primary school was chosen for the application of the experiment. Two sections has been chosen randomly to represent the experimental and the control group , twenty foure female pupils and twine- one female pupils in each group . The two groups have been equivalent on the following variables: (age, achievement in mathematics, previous knowledge and intelligence). The experimental group was taught according to SCAMPER while the conventional method was used with the control group the researcher has taught both groups by herself. In order to measure the In order to measure the level of acquisition of creative thinking , the researcher has prepared achievement test which consists of ( 40 ) multiple choice items of four alternatives distributed over the first three levels of Bloom’s classification (knowledge ,comprehension, application) . Face validity of the test has been calculated through exposing the test items to a jury of specialists. Reliability has been calculated by using Kuder – Richardson Formula 20 (KR - 20) which is (88 %) . The null hypotheses have been set of the test and the statistical treatment of the data using ( t – test ) for two independent samples , the results have been the following : The achievement of the experimental group is more than that of the control group in the achievement test.. In the light of the results, the researcher recommended the use of (SCAMPER) when teaching mathematical concepts to Fifth Year pupils at the primary stage and train their teachers in how to use this Strategy . The researcher has suggested adopting identical studies to the current study put it should be applied on different stages and topics with new variables.